1994
DOI: 10.1677/jme.0.0130253
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mRNA for follistatin and inhibin/activin subunits during follicular growth and atresia

Abstract: The aim of the present study was to investigate the sites and time of follistatin and inhibin alpha and beta A subunit gene expression during ovine follicular development and atresia. Prepubertal ovaries of 2-, 8- and 14-week-old ewe lambs (n = 9) were used. Regardless of age, the ovaries contained many follicles at different stages of development up to 2 mm in diameter, but large antral follicles were not found. Ovarian sections were hybridized with 35S-labelled antisense RNA probes transcribed from follistat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 36 publications
(65 reference statements)
4
29
0
1
Order By: Relevance
“…Immunostaining intensity was weak to moderate in pre-antral stages and strongest at the antral stage, confirming that the mature large follicles are the major source of inhibin in goats and that the pre-antral follicles contribute minimally to inhibin production. Further confirmation of this is provided by the presence of mRNA encoding inpresence of mRNA encoding inpresence of mRNA encoding inhibin α and β A in the granulosa cells of most pre-antral and all non-atretic antral follicles, and its absence in primordial follicles or primary follicles with less than two layers of granulosa cells [1]. Furthermore, the amounts of mRNAs for inhibin α and β A subunits increased coincident with follicle size, whereas inhibin β A mRNAs remained unchanged [10].…”
Section: Discussionmentioning
confidence: 76%
“…Immunostaining intensity was weak to moderate in pre-antral stages and strongest at the antral stage, confirming that the mature large follicles are the major source of inhibin in goats and that the pre-antral follicles contribute minimally to inhibin production. Further confirmation of this is provided by the presence of mRNA encoding inpresence of mRNA encoding inpresence of mRNA encoding inhibin α and β A in the granulosa cells of most pre-antral and all non-atretic antral follicles, and its absence in primordial follicles or primary follicles with less than two layers of granulosa cells [1]. Furthermore, the amounts of mRNAs for inhibin α and β A subunits increased coincident with follicle size, whereas inhibin β A mRNAs remained unchanged [10].…”
Section: Discussionmentioning
confidence: 76%
“…In follicles where such a section could not be found, diameters were measured in the largest estimated cross-section. Antral follicles were examined for the presence of pycnotic and/or apoptotic cells and classified as non-atretic, early atretic (stage I), advanced (stage II) and late atretic (stage III) according to Braw-Tal (1994). Briefly, follicles designated as non-atretic were those with occasional mitotic figs and none or up to five pycnotic/apoptotic nuclei among the granulosa cells.…”
Section: Follicle Classificationmentioning
confidence: 99%
“…Within the ovary, the granulosa cells in antral follicles and luteinized granulosa cells are the main sites that express follistatin mRNA and protein, whereas other structures, such as the theca cells, stroma and oocytes, appear to be devoid of follistatin mRNA (Shimasaki et al, 1989;Roberts et al, 1993;Braw-Tal, 1994;Tisdall et al, 1994), although follistatin mRNA has been observed in human oocytes (Sidis et al, 1998). However, follistatin protein was detected in the theca cell layers of human small antral follicles in the absence of follistatin mRNA expression, but then became undetectable with the development of a dominant follicle (Roberts et al, 1993).…”
Section: Location and Secretion Of Follistatinmentioning
confidence: 99%
“…Moreover, the follistatin protein appears to be present in only the selected dominant follicles (Nakatani et al, 1991). At the same time, primordial through to primary follicles do not express follistatin mRNA (Kogawa et al, 1991;Braw-Tal, 1994;Tisdall et al, 1994), implying that follistatin may not be involved in the initial stage of recruitment of follicles. Species differences occur, as the expression of follistatin is maintained in the corpus luteum in primates, whereas in other species, expression falls markedly after ovulation in the developing corpus luteum (Kogawa et al, 1991;Roberts et al, 1993;Wada et al, 1996).…”
Section: Location and Secretion Of Follistatinmentioning
confidence: 99%